Effect of 1-methylcyclopropene on flat peach fruit quality based on electronic senses, LC-MS, and HS-SPME-GC-MS during shelf storage. (1st January 2023) - Zhang, Xianan; Su, Mingshen; Zhou, Huijuan; Leng, Feng; Du, Jihong; Li, Xiongwei; Zhang, Minghao; Hu, Yang; Gao, Yu; Ye, Zhengwen
Abstract: The effects of 1-methylcyclopropene (1-MCP) on the sensory quality of the 'Yulu' flat peach fruit were determined using electronic tongue, electronic nose, LC-MS/MS, and HS-SPME-GC-MS. A total of 90 taste compounds and 49 volatile compounds were quantified. Of these, 15–21 types of aroma compounds with odor activity values (OAV) > 1 were considered as the most significant volatiles. 1-MCP significantly affected the levels of soluble sugars, organic acids, free amino acids, phenolics, amygdalin, and volatile compounds. 1-MCP slowed the increase in alanine and γ-aminobutyric acid in fruit during ripening and senescence. 1-MCP also increased the level of proline in fruits, and decreased that of glutamic acid, glutamine, and serine. 1-MCP significantly inhibited the decline in procyanidins after six to ten days of storage. During fruit senescence, the level of free esters markedly increased; however, 1-MCP reduced this level. Fruits treated with 1-MCP contained more β-myrcene and linalool and fewer lactones. β-Damascenone, (E)-2-nonenal, (E)-2-hexenal, γ-decalactone had the highest OAVs. The PCA biplot revealed that fruit shelf-life duration had a greater effect on taste than 1-MCP, while 1-MCP had a greater impact on aroma. Our findings provide a basis for the use of 1-MCP to preserve flat peaches in the future. Highlights: Taste and aroma were profiled by electronic senses, LC-MS/MS, and HS-SPME-GC-MS. Fruit shelf-life duration had a greater effect on taste than 1-methylcyclopropene (1-MCP). Flavor-related primary and secondary metabolites in fruits were markedly affected by 1-MCP. 1-MCP had a greater effect on aroma than taste.